Numerical study on supercritical heat transfer of n-decane during pyrolysis in rectangular tubes. (April 2020) - Lei, Zhiliang; He, Kuo; Huang, Qin; Bao, Zewei; Li, Xiangyuan
Highlights: The effect of equivalent diameter on heat transfer with pyrolysis was discussed. The effect of pyrolysis on supercritical heat transfer was discussed. The relation between thermophysical property and heat transfer was examined. The heat transfer correlation with pyrolysis for rectangular tubes was proposed. Abstract: The supercritical heat transfer processes of n-decane during pyrolysis in rectangular tubes having three different equivalent diameters are studied numerically. The effects of mass flow rate (2–5 g/s), heat flux (109–436 kW/m 2 ), and three different channel configurations having the same cross-sectional areas on the supercritical heat transfer characteristics of n-decane during pyrolysis are investigated. The heat transfer mechanisms are analysed from the perspective of pyrolysis, thermophysical properties, wall shear stress, and thickness of the boundary layer. The results demonstrate that the heat transfer coefficient increases with mass flow rate. The heat transfer coefficient decreases with increasing heat flux at the inlet section of the heating tube; however, the trend is reversed after a certain distance. The heat transfer coefficient decreases with the increase in the equivalent diameter. The thinning of the boundary layer thickness, increase in the wall shear stress, primary pyrolysis reaction, increase in the heat capacity and thermal conductivity, and decrease in the viscosity enhance the heat transfer. Based on the considerable deviations between the computational fluid dynamics simulation results and the existing heat transfer correlations, the Dittus–Boelter correlation is modified such that it can be applied to predict the supercritical heat transfer coefficients of n-decane during pyrolysis in the above rectangular tubes.